Vaccinating Adult Patients with Cirrhosis: Trends over a Decade in the United States - Abhijeet Waghray; Nisheet Waghray; Hicham Khallafi; K. V. Narayanan Menon (Gastroenterology Research and Practice)
Introduction. The progression of chronic liver disease to cirrhosis involves both innate and adaptive immune system dysfunction resulting in increased risk of infectious complications. Vaccinations against pneumococcus, hepatitis A virus (HAV), and hepatitis B virus (HBV) are well tolerated and effective in disease prevention and reduction in morbidity and mortality. Prior studies assessing vaccination rates in patients with cirrhosis have specific limitations and to date no study has provided a comprehensive evaluation of vaccination rates in patients with cirrhosis in the United States. Aim. This study assessed vaccination rates for pneumococcus, HAV, and HBV in patients with cirrhosis. Results. Overall 59.7% of patients with cirrhosis received at least 1 vaccination during the study period. Vaccination rates within the same or following year of cirrhosis diagnosis were 19.9%, 7.7%, and 11.0% against pneumococcus, HAV, and HBV, respectively. Trend analysis revealed significant increases in vaccination rates for pneumococcus in all patients with cirrhosis and within subgroups based on age, gender, and presence of concomitant diabetes. Conclusion. The study demonstrated that vaccination rates in patients with cirrhosis remain suboptimal. Ultimately, the use of electronic medical record (EMR) reminders improved communication between healthcare professionals and public health programs to increase awareness are fundamental to reducing morbidity, mortality, and health-care related costs of vaccine preventable diseases in patients with cirrhosis.